An Empirical Analysis of Barriers and Strategic Pathways for Unbanked Entrepreneurs in Nepal: A Pilot Study - KC, Amit; Shrestha, Hira Lal (NPRC Journal of Multidisciplinary Research, 2025)
Background: Smaller entrepreneurs are considered indispensable in the developmental economy of emerging countries such as Nepal, but a substantial portion of them are left out of the financial system. Objectives: • To examine financial literacy among small entrepreneurs. • To highlight major obstacles in getting access to banking institutions. • To analyze the viability of digital financial solutions and microfinance institutions. • To comprehend awareness and effectiveness of government schemes. Methods: A cross-sectional study using a structured format with a population of 50 small shopkeepers in Sukedhara, Kathmandu, was used. Data analysis included descriptive statistics, Cronbach’s Alpha Test in SPSS for reliability, and a Pearson Correlation Test for four major hypotheses. Findings: Lack of financial literacy (r=0.68, p<0.01) and geographical restrictions (r=0.72, p<0.01) were strongly related to financial exclusion and informal financial participation. M-banking had a great potential for financial inclusion (r=0.61, p<0.01) but this was conditional on digital literacy. Awareness of government schemes was a critical factor where no important relationship with better access existed (r=0.19, p>0.05). Conclusion: The financial gap is perpetuated by interwoven demand side (literacy, perception) and supply side (access, product) barriers. Implementation: To make this vision a reality, a synergistic approach can be adopted, which will include the following: (1) Financial and digital literacy programs at a national level; (2) Improving mobile banking infrastructure and trust; (3) Improving public-private credit guarantee schemes and awareness thereof; and (4) Banks developing new products based on an alternative credit.